An ethnographic study of illness causation perceptions of Yemeni-Americans - Kulwicki, Anahid (1991)
Kulwicki, A. N. A. H. I. D. (1991). An ethnographic study of illness causation perceptions of Yemeni-Americans. Michigan Academician, 23(1), 31-42.